Assessment of Thyroid-Stimulating Hormone (TSH) Reports: Insights into Population-Level Thyroid Health - Mynumathi M; Andria V; Aishwarya B; Prasanth N; Kavya K (Archives of Endocrinology and Disorders, 2026)
Background: Thyroid-Stimulating Hormone (TSH) is a sensitive biomarker of thyroid function and plays a critical role in regulating metabolism, growth, reproduction and overall endocrine health. Abnormal TSH levels are associated with thyroid disorders that can lead to significant health complications if left untreated. Objective: To evaluate serum TSH levels among patients undergoing routine thyroid function testing and assess the prevalence of thyroid abnormalities within the study population. Methods: A retrospective analysis was conducted on 41 patient TSH reports obtained through routine laboratory testing. Blood samples were collected in gel tube vacutainers, transported under controlled conditions and processed following standard laboratory protocols. Serum TSH levels were measured using the Chemiluminescent Enzyme Immunoassay (CLEIA) method on the COBAS e411 analyzer. Descriptive statistical parameters, including mean, median, standard deviation, range and quartiles, were calculated. Results: TSH values ranged from 0.085 to >100.000 µIU/mL. The mean TSH level was 7.88 µIU/mL, while the median was 4.14 µIU/mL. Elevated TSH levels suggestive of hypothyroidism were observed in 20 patients (48.8%), whereas one patient (2.4%) exhibited a suppressed TSH level indicative of possible hyperthyroidism. Normal TSH values were recorded in 20 patients (48.8%). The standard deviation of 16.20 µIU/mL and range of 99.92 µIU/mL indicated substantial variability in thyroid function across the study population. Conclusion: Nearly half of the participants demonstrated elevated TSH levels, indicating a considerable prevalence of thyroid dysfunction. Routine TSH screening and monitoring are essential for early detection and management of thyroid disorders. Larger studies incorporating free T3 and free T4 measurements are recommended to improve diagnostic accuracy and support population-specific reference ranges.